2013
DOI: 10.1002/ajh.23386
|View full text |Cite
|
Sign up to set email alerts
|

Deferiprone (GPO‐L‐ONE®) monotherapy reduces iron overload in transfusion‐dependent thalassemias: 1‐year results from a multicenter prospective, single arm, open label, dose escalating phase III pediatric study (GPO‐L‐ONE; A001) from Thailand

Abstract: Accessibility to iron chelators including deferoxamine and deferasirox remains obscured in many developing countries. To provide an alternative, the government pharmaceutical organization of Thailand (GPO) manufactured deferiprone which has similar bioequivalent to the standard product. Seventy-three pediatric patients with severe b thalassemias, age range 3.2-19 years, were recruited to a 1-year multicenter prospective, single arm, open label, dose escalating Phase III study of deferiprone to determine its cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 53 publications
3
40
1
Order By: Relevance
“…Although serum ferritin alone is not the best marker to reflect the total body iron status [37], sequential measurements represent a trend of the body iron burden. A recent 1-year study by Viprakasit et al [17] on the efficacy of monotherapy with generic DFP (GPO-L-ONE) demonstrated that only 45.2% of patients responded to treatment (reducing serum ferritin >15%) and the most significant serum ferritin base response is expected among those who have the highest initial serum ferritin level. Interestingly, our current study shows that, over 3-year study period, patients with initial serum ferritin in the so-called ‘mid range' (>2,500-4,000 ng/ml) had the most significant fall in serum ferritin (final ferritin level of 874.9 ng/ml), which exceeded the decreases in the other two groups with lower or higher initial serum ferritin levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although serum ferritin alone is not the best marker to reflect the total body iron status [37], sequential measurements represent a trend of the body iron burden. A recent 1-year study by Viprakasit et al [17] on the efficacy of monotherapy with generic DFP (GPO-L-ONE) demonstrated that only 45.2% of patients responded to treatment (reducing serum ferritin >15%) and the most significant serum ferritin base response is expected among those who have the highest initial serum ferritin level. Interestingly, our current study shows that, over 3-year study period, patients with initial serum ferritin in the so-called ‘mid range' (>2,500-4,000 ng/ml) had the most significant fall in serum ferritin (final ferritin level of 874.9 ng/ml), which exceeded the decreases in the other two groups with lower or higher initial serum ferritin levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, the price of this medication is unaffordable for most patients. Deferiprone (DFP), a cheaper oral iron chelator proven effective in achieving a negative iron balance in many short- and long-term clinical trials in adult patients with iron overload[3,4,5,6,7,8,9], has recently been studied for its efficacy and safety in thalassemia children receiving chelation [10,11,12,13,14,15,16,17]. To improve the efficacy of chelation treatment, the ‘iron shuttle hypothesis' [18,19] has been proposed, leading to many studies on the combined use of DFP and DFO [10,11,20,21,22,23,24,25,26,27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…7 Serious adverse event (SAE) An AE was considered serious, if one of the following criteria were met: results in death, is life-threatening (at time of occurrence), requires or prolongs existing hospitalization, results in disability or incapacity, or results in congenital abnormality. 8 Additionally, the following important and severe medical events were always considered as serious: acute liver failure, acute renal failure, acute respiratory failure, agranulocytosis (neutrophil count less than 0.5x10 9 /L), anaphylaxis, any malignancy, aplastic anemia, elevated liver enzymes (alanine transaminase (ALT) or aspartate transaminase (AST) more than five times baseline values), liver necrosis, malignant hypertension, neutropenia (neutrophil count less than 1.5x10 9 /L), pulmonary fibrosis, pulmonary hypertension, sclerosing syndromes, seizure (only central neurological seizures), thrombocytopenia (platelet count <150x10 9 /L), torsades de pointes, toxic epidermal necrolysis, ventricular fibrillation. Severity…”
Section: Methodsmentioning
confidence: 99%
“…Similar observations have been reported before. 1,8,9 Ethnic differences may influence the occurrence of agranulocytosis as reported in Chinese children on DFP. 10 Combined therapy was not associated with a higher risk for neutropenia consistent with existing data.…”
Section: /9mentioning
confidence: 99%
See 1 more Smart Citation